Comparação do Strain Global Longitudinal pelo Ecocardiograma Bidimensional em gestantes com diagnóstico clínico de pré-eclâmpsia e em gestantes sem pré-eclâmpsia - Renata Felício Braga Paulino (2023)
Preeclampsia is a serious condition that affects pregnant women worldwide and causes increased maternal and fetal morbidity and mortality as well as increased future cardiovascular risk. The pathophysiology is multifactorial and the identification of causes associated with increased cardiovascular risk is still a challenge. The Analysis of left ventricular longitudinal global strain (LVLGS) by speckle tracking transthoracic echocardiography (STE) has been considered capable of identifying early ventricular dysfunction with potential for risk stratification and possibly follow-up of these women. Preliminary data on the usefulness of the LVLGS technique as a marker of early myocardial dysfunction in patients with preeclampsia have shown promise. The hypothesis of the present study was that LVLGS performed by STE is reduced in women with preeclampsia. Thus, the aim of this study was to evaluate LVLGS in patients with preeclampsia, comparing the strain values in pregnant women without comorbidities. For this purpose, a cohort, cross-sectional, observational study was performed with patients from the terciary Hospitals. Pregnant women,age ≥ 18 years, without previous heart disease and with images suitable for strain analysis were included. The patients underwent clinical data collection and echocardiographic study up to 14 days after diagnosis of preeclampsia. A total of 32 patients were initially selected, and 26 patients were included in the final analysis of this study. The median age was 33.5 [30.8-36.3] years for the case group and 30.0 [30-35] years for the control group. The median gestational age at the first echocardiogram was 33 [28.8- 34.3] weeks in the case group and 31.5 [27.8-35] weeks in the control group. All patients had preserved LV ejection fraction at inclusion, both by the Teichholz method in case group [68,5% (64,8 – 73,0)] vs control[ 67,0% (63,0–71,0)] and by the Simpson method in case group[ 64,0% (60,0–67,0) vs control 65,0% (62,0–67,0 64.5 ± 4.4) and there were no significant changes in this parameter during follow-up. Despite the preserved LV ejection fraction, the value of the LVGLS was reduced for the case group 19,0% (16,5–21,0)] and preserved for the control group 21,4% (20,5–23,8); p<0,001 being further reduced in patients with early preeclampsia [18,5% (16,4-20,8 ).Regarding the strain of the case patients and strain after delivery,there was a significant improvement in this value in early PE subgroup (<34s), with a median of 18.5% (16.4-20.8) at PE diagnosis and 20.9% (18.3-22.4) in the puerperium group; p=0.013). In conclusion, the results demonstrated a significant difference between the LVGLS values of PE patients compared to pregnant women without comorbidities with improvement after delivery, in patients with early preeclampsia (<34s),showing alterations in the myocardium, even when the left ejection fraction is still normal.